Analisis Indikator Hambatan Dalam Pelaksanaan Proyek Konstruksi Gedung - Fazal, Bustanul -; Meliyana, Meliyana; Siviana, Mery (Jurnal Teknik Sipil Unaya, 2025)
This study aims to determine the indicators of obstacles that occur and the dominant indicators of obstacles that occur in the implementation of building construction projects in the city of Banda Aceh. Barriers to implementing building construction projects were evaluated by 30 indicators from empirical studies. This study uses a quantitative method approach through questionnaires. The respondent criteria is one of the contractor company personnel at the top management level which is limited to project manager/site manager/site engineer/supervisor. The population was 214 contractor companies and the sample was 68 contractor companies. The sampling technique used was purposive sampling. The data analysis technique used descriptive statistics. The results of the research show that there are 23 indicators that occur in the implementation of building construction projects in Banda Aceh City, of which the level rarely occurs is 10 indicators, the level sometimes occurs is 9 indicators, and the level frequently occurs is 4 indicators. The dominant obstacle indicator that occurs in the implementation of building construction projects in Banda Aceh City is the failure to define risks clearly with a mean value of 3.794.